Advancing the Modeling of Future Climate and Innovation Impacts on Perennial Crops to Support Adaptation: A Case Study of California Almonds - Shuaiqi Wu; Prudentia Gugulethu Zikalala; Sequoia Alba; Katherine S. Jarvis‐Shean; Isaya Kisekka; Mira Segaran; Richard Snyder; Erwan Monier (Earth's Future)
Abstract Perennial crops are vital to the global food supply, providing valuable nutrition and economic benefits, but are at risk of severe climate damages. Most climate research has focused on major annual crops like cereals and has focused on the overall impact of climate change on yields providing limited actionable knowledge to support adaptation. In this study, we bring together climate scientists, biometeorology specialists, plant scientists, and agricultural engineers to develop a new perennial crop modeling framework that integrates climate modeling, horticulture and agronomy science, and statistical modeling. We apply this framework to California almonds as a case study, because they offer robust data to calibrate and evaluate our model. Our model quantifies the influence of climate in each almond development stage and of innovation on county‐level yields. We simulate future yield changes under a large multi‐model ensemble of high‐resolution climate simulations and innovation scenarios. We find that climate change could lead to yield losses of 17% by 2100 under moderate warming (SSP245) and 49% under high warming (SSP585); however, we also find that sustained innovation gains could more than offset these negative climate impacts. We identify increasing minimum temperatures and humidity during the bloom and pollination period as well as heat stress during the growing period as the main drivers of yield losses. We discuss synergistic strategies to limit the negative impacts of climate change and to ensure continued gains from innovation. This modeling approach could provide valuable insights into climate adaptation strategies for other perennial crops and regions.